2015
DOI: 10.5614/j.math.fund.sci.2015.47.3.3
|View full text |Cite
|
Sign up to set email alerts
|

Embryo Incision as a New Technique for Double Seedling Production of Indonesian Elite Coconut Type “Kopyor”

Abstract: Abstract.One of the present major limitations of seedling production of kopyortype coconut using embryo culture is that only one seedling can be produced from a single embryo. Therefore, we report on the development of a new breakthrough technique for the production of double seedlings from a single embryo. The technique consists of four steps, viz. (i) germination; (ii) incision; (iii) splitting; and (iv) recovery. A histological study was carried out on the development of the halved embryo into a new shoot. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…N'Nan et al [35] concluded that cryopreservation of Cocos nucifera embryos after silica gel drying is feasible and facilitates phytosanitary control for the establishment of germplasm collections. Similarly, Sisunandar [36] observed that embryo maturity is related to germination rates and complete plant formation in Cocos nucifera embryos subjected to LN. Cryopreservation of seeds with Elaeis guineensis integument proved effective, suggesting that rescuing zygotic embryos or using cryoprotectants may not be necessary [37].…”
Section: Cryopreservation Of Zygotic Embryosmentioning
confidence: 86%
“…N'Nan et al [35] concluded that cryopreservation of Cocos nucifera embryos after silica gel drying is feasible and facilitates phytosanitary control for the establishment of germplasm collections. Similarly, Sisunandar [36] observed that embryo maturity is related to germination rates and complete plant formation in Cocos nucifera embryos subjected to LN. Cryopreservation of seeds with Elaeis guineensis integument proved effective, suggesting that rescuing zygotic embryos or using cryoprotectants may not be necessary [37].…”
Section: Cryopreservation Of Zygotic Embryosmentioning
confidence: 86%
“…banana 36 , ensete 37 & pitaya 38 , these techniques proved to be ineffective in coconut. Sisunandar and coworkers developed an embryo incision method that when combined with the addition of cytokinins in the medium, resulted in only two cloned plantlets per embryo 39 . Our results significantly differed from this report in two ways; firstly the plantlets that were cut in two, both in the presence and absence of TDZ, always resulted in the death of one part.…”
Section: Discussionmentioning
confidence: 99%
“…Teknik kultur in vitro kelapa kopyor melalui kultur penyelamatan embrio (embryo rescue) saat ini umum digunakan di Indonesia untuk menghasilkan bibit kelapa kopyor (Tahardi & Warga-Dalem, 1982;Mashud & Manaroinsong, 2007;Sukendah et al, 2008;Sisunandar, 2011;Sisunandar et al, 2015). Tahapan kultur embrio kelapa kopyor dimulai dari perkecambahan embrio, perkembangan tunas, pembentukan akar, pembesaran planlet, dan aklimatisasi.…”
Section: Pendahuluanunclassified